The role of indeterminate fine‐needle biopsy in the diagnosis of parotid malignancy. (2nd October 2013) - Fundakowski, Christopher; Castaño, Johnathan; Abouyared, Marianne; Lo, Kaming; Rivera, Andrew; Ojo, Rosemary; Gomez‐Fernandez, Carmen; Messinger, Shari; Sargi, Zoukaa
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To examine the significance of indeterminate fine needle aspiration biopsy in the diagnosis of parotid gland malignancy. Study Design Retrospective case series, academic tertiary referral center. Methods A total of 559 parotidectomies performed between the years of 2005 and 2010 were reviewed, with 56.7% (N = 317) meeting investigation eligibility criteria: primary parotid tumor, availability of fine‐needle aspiration biopsy, intraoperative frozen section, and final pathologic diagnosis. One‐hundred fifteen (n = 115, 36.3%) of the 317 parotid biopsies were interpreted as indeterminate. Clinical history, physical examination, operative findings, and histopathologic characteristics were analyzed. Multiple logistic regression, with deviation from means coding, was used to estimate the odds of malignancy in the indeterminate group and provide a comparison with reference to the average odds of malignancy over the overall sample. Results Overall final pathologic distribution of parotid masses (N = 317) was 82.3% benign and 17.7% malignant. Overall final pathologic distribution of parotid masses in the indeterminate group (n = 115) was 31.3% malignant and 68.7% benign. In comparison, the overall group (N = 317) had a decreased comparative percentage of malignant specimens at 17.7%. Interestingly, in the instance of an indeterminate biopsy, the odds of having a malignancy was estimated to increase by 1.98‐fold compared to overall mean odds of malignancy in the sample. Other statistically significant clinical predictors of parotid malignancy included history of prior malignancy, current tobacco user, locally invasive characteristics intraoperatively, and facial nerve involvement intraoperatively. Conclusions In the context of an indeterminate fine‐needle aspiration biopsy, an elevated index of suspicion for parotid malignancy may be warranted. Level of Evidence 4. Laryngoscope, 124:678–681, 2014